Invasive Candida Infections and the Harm From Antibacterial Drugs in Critically Ill Patients. Issue 3 (March 2015) - Jensen, Jens-Ulrik S.; Hein, Lars; Lundgren, Bettina; Bestle, Morten H.; Mohr, Thomas; Andersen, Mads H.; Løken, Jesper; Tousi, Hamid; Søe-Jensen, Peter; Lauritsen, Anne Ø.; Strange, Ditte; Petersen, John A.; et al.
<x xml:space="preserve">Abstract</x> Objective: Use of antibiotics in critically ill patients may increase the risk of invasive Candida infection. The objective of this study was to determine whether increased exposure to antibiotics is associated with increased prevalence of invasive Candida infection. Design: Substudy using data from a randomized controlled trial, the Procalcitonin And Survival Study 2006–2010. Setting: Nine multidisciplinary ICUs across Denmark. Patients: A total of 1, 200 critically ill patients. Intervention: Patients were randomly allocated to either a "high exposure" antibiotic therapy (intervention arm, n = 604) or a "standard exposure" guided by current guidelines (n = 596). Measurements and Main Results: Seventy-four patients met the endpoint, "invasive Candida infection, " 40 in the high exposure arm and 34 in standard exposure arm (relative risk = 1.2; 95% CI, 0.7–1.8; p = 0.52). Among medical patients in the high exposure arm, the use of ciprofloxacin and piperacillin/tazobactam was 51% and 75% higher than in the standard exposure arm; no difference in antibiotic exposure was observed between the randomized arms in surgical patients. Among medical intensive care patients, invasive Candida infection was more frequent in the high exposure arm (6.2%; 27/437) than in standard exposure arm (3.3%; 14/424) (hazard ratio = 1.9; 95% CI, 1.0–3.6; p = 0.05). Ciprofloxacin used at study entry independently predicted invasive Candida infection (adjusted hazard ratio = 2.1 [1.1–4.1]); the risk gradually increased with duration of ciprofloxacin therapy: six of 384 in patients not exposed (1.6%), eight of 212 (3.8%) when used for 1–2 days (hazard ratio = 2.5; 95% CI, 0.9–7.3), and 31 of 493 (6.3%) when used for 3 days (hazard ratio = 3.8; 95% CI, 1.6–9.3; p = 0.002). Patients with any ciprofloxacin-containing antibiotic regimen the first 3 days in the trial had a higher risk of invasive Candida infection than did patients on any antibiotic regimen not containing ciprofloxacin (unadjusted hazard ratio = 3.7; 95% CI, 1.6–8.7; p = 0.003; adjusted hazard ratio, 3.4; 95% CI, 1.4–8.0; p = 0.006). Conclusions: High exposure to antibiotics is associated to increased risk of invasive Candida infection in medical intensive care patients. Patients with ciprofloxacin-containing regimens had higher risk of invasive Candida infection. Other antibiotics, such as meropenem, piperacillin/tazobactam, and cefuroxime, were not associated with such a risk.